'I don't know what a proper woman means': what women with intellectual disabilities think about sex, sexuality and themselves. (28th November 2011) - Fitzgerald, Christina; Withers, Paul
<x xml:space="preserve">Abstract</x> Accessible summary For a long time, people tried to stop women with intellectual disabilities from knowing about sex and from having sex. We talked to some women with intellectual disabilities to find out what they thought about sex. Many of the women told us that they thought sex is bad and that they should not do it. We want people to be able to help women with intellectual disabilities to feel confident to make choices about sex. Summary There is very little literature concerning how women with intellectual disabilities conceptualise their sexuality or develop a sexual identity. Semi‐structured interview schedules were used to guide interviews with 10 women with intellectual disabilities. Thematic analysis was used to analyse the interview transcripts. Many of the women could not conceptualise themselves as sexual beings, and they tended to regard sex as a dirty and inappropriate activity for them. They generally believed that other people prohibited them from engaging in sexual activity. The women often considered themselves to be of little value, and the majority had no clear sense of identity. It is incumbent upon services to find the means to empower women with intellectual disabilities to acknowledge, welcome and take control of their own sexuality.